Effects of Perceived Risk on Online Buying Behavior - Pandey, Diwakar (Dibyajyoti Journal, 2025)
This study aims to investigate the impact of perceived risk factors on online purchasing behavior. The two main factors taken from the extensive review are financial risk and product risk. The web-based Google Form survey was administered, and a total of 194 online shoppers. The statistical analysis showed that financial risk only has a direct significant impact online shopping behavior of the respondents. The study will assist online shopping in the context of urban areas when markers accommodate its result in marketing policy.